Pomysły ziemiańskie dotyczące rozwoju przemysłu w Królestwie Polskim w okresie międzypowstaniowym. Teoria i praktyka - Kita, Jarosław (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
The research problem definite with the title of present article was captured in several aspects. Firstly, what was landowner’s relations in issue of industrialization, for special consideration grounds, which created Polish Kingdom. Second matter are landowners’ ideas regarding to industrialization, so in narrow range, that is landowner’s goods, as in wider dimension, that is a space of Polish Kingdom. However, third problem is matter of possibility and scale of realization those ideas in period between uprisings, that is on how much the representatives of territorial community joined into working on thing of industries development in this period. The subject was worked out first of all on the basis of specific and homogeneous source basic, and namely landowner’s press in period between uprisings. Therefore author’s intention is not straighten generalizing reflection this phenomenon, and a main goal is just a bringing closer this problem, basing on limited source base and resulting from this source an arrangement research.